2012
DOI: 10.1179/1743294411y.0000000077
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and kinetics of nitriding of pure titanium and Ti–6Al–4V in molten salt bath of potassium nitrate

Abstract: Surface nitriding of pure Ti and Ti-6Al-4V alloy was performed in potassium nitrate molten salt bath at temperatures ranging from 600 to 700uC for 2-18 h. The formation of a compound nitride layer comprising of e-Ti 2 N and d-TiN phases was identified with thicknesses of 1-12 mm for pure Ti and 1-6 mm for Ti-6Al-4V respectively. Ti-6Al-4V was found to develop an oxide phase upon nitriding for .8 h at 700uC. Maximum hardness values of 1470 HV for pure Ti and 1367 HV for Ti-6Al-4V were achieved. Under identical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…From the Reaction 4, it can be known that, at the temperature of 550°C [14], CNOˉ can decompose into the active N atoms, along with the CNˉ, carbonate ( ) and carbon monoxide (CO); meanwhile, CO can decompose into the active carbon (C) atoms, along with the carbon dioxide (CO 2 ), as shown in Reaction 5. According to the Reactions 4 and 5, it can be found that when CNOˉ provides the active N atom, CNˉ would also be generated; furthermore, with the treatment time increasing, the content of CNˉ would be increased accordingly, which would directly threaten the health of operators and damage the environment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the Reaction 4, it can be known that, at the temperature of 550°C [14], CNOˉ can decompose into the active N atoms, along with the CNˉ, carbonate ( ) and carbon monoxide (CO); meanwhile, CO can decompose into the active carbon (C) atoms, along with the carbon dioxide (CO 2 ), as shown in Reaction 5. According to the Reactions 4 and 5, it can be found that when CNOˉ provides the active N atom, CNˉ would also be generated; furthermore, with the treatment time increasing, the content of CNˉ would be increased accordingly, which would directly threaten the health of operators and damage the environment.…”
Section: Resultsmentioning
confidence: 99%
“…After that, the nitriding agent was packed in a crucible, ensuring a sufficiently thick pack around the treated sample. Furthermore, to reduce the effect of nitriding temperature on the microstructural characteristics of the titanium matrix and ensure the growth of the nitride layer, after deeply analysing the current research about the salt bath nitriding of titanium alloy [14,15], the nitriding temperature and time are determined to be 550°C and 7 h (shown in Table 2), respectively. Then, the nitriding experiments were performed in a box-type resistance furnace; after the treatments, samples were taken out and cooled by air.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations